Multimedia Interaktif 3 Dimensi Pengenalan Stasiun Luar Angkasa International Space Station (Iss) - Lalu Jayeng rusiandi Putra; Danang Tejo Kumoro (Universitas Bumigora, 2019)
International Space Station (ISS) is one of the greatest achievements in modern science especially in astronomy and engineering. The main function of the ISS is as an aerospace laboratory to conduct research and experiments related to the space environment which can not be done on earth. For the students in high schools, especially in MA Nurul Iman, there are still many who do not know the existence and function of the details of International Space Station (ISS). Therefore, it needs an interactive recognition media where users can see and know the function of the ISS more clearly and more interactive than the video or print media. The result of this thesis is an interactive multimedia introduction of International Space Station (ISS) International Space Station (ISS) the ISS and the ISS station parts functions. The results that can be drawn from making this application are effective for use as information medium introducing International Space Station (ISS).